La potestad disciplinaria en la administración y la prescripción para el inicio de los procedimientos - Sáenz Carbonell, Jorge Francisco (2014)
Although the General Law of Public Administration contains detailed provisions regarding the administrative procedure, it has some degree of indeterminacy about the time a government department has to start a procedure against a civil servant, without giving him the opportunity to invoke the statute of limitations. The problems arising from this have been solved by principle-based decisions of the Second Court of Cassation.